Lithium‐cyclopropylethinylamidinates1. Issue 14 (8th October 2013) - Sroor, Farid M. A.; Hrib, Cristian G.; Hilfert, Liane; Edelmann, Frank T.
Abstract A series of six new lithium‐cyclopropylethinylamidinates, Li[c‐C3H5–C≡C–C(NR)2]·S (R = iPr, S = Et2O (2a), THF (2b), DME (2c); R = cyclohexyl (Cy), S = Et2O (3a), THF (3b), DME (3c)) were prepared and fully characterized. The synthetic protocol involves in situ‐deprotonation of commercially available cyclopropylacetylene followed by treatment with either N, N′‐diisopropylcarbodiimide or N, N′‐dicyclohexylcarbodiimide. The cyclopropyl substituent exerts a significant influence on the 13C NMR spectroscopic shift of the acetylenic carbon atom to which it is bound. X‐ray diffraction studies of 2b and 3b revealed that in the solid state the new lithium amidinates adopt ladder‐type dimeric molecular structures.